PERANCANGAN BUKU CERITA BERGAMBAR GALODO BUKIT TUI TAHUN 1987 - Adzkia Yuska (IAM Indonesia, 2023)
Tui Hill is a limestone hill which is an asset for the people of Padang Panjang city. Tui Hill has a gripping history for the local community due to the occurrence of galodo in 1987. This incident occurred on May 4, 1987 which coincided with the month of Ramadan. This design will be used as a picture story book as a medium in telling the 1987 Bukit Tui galodo incident. A picture story book is a book that uses pictures to visualize a storyline. This design departs from a problem where a group of youths like to do bad things even in the month of Ramadan so that the belief arises that the Bukit Tui galodo incident is a form of God's anger against the group. With media illustrations, the audience will be able to see an overview of the 1987 Bukit Tui galodo. The method used to solve this problem uses the 5W+1H method. The main media for this design is in the form of picture story books and the supporting media for this design are t-shirts, tote bags, hats, key chains, stickers, notebook, banner, table, artset, bookmark, puzzle and posters. Keywords: Design, Books, Picture Stories, Galodo, Tui Hill